P114 Ionising radiation inhibits inflammation in patients with musculoskeletal diseases: radon treatment vs low-dose radiation therapy. (21st February 2018) - Shreder, K; Cucu, A; Kraft, D; Lehrian, S; Kondol, J; Klein, G; Frey, B; Gaipl, U; Fournier, C
Abstract : Introduction: Rheumatoid arthritis (RA) and osteoarthritis (OA) are the most common musculoskeletal diseases (MSD) that affect the joints. Reduced mobility and quality of life are the consequences of the cartilage and bone tissue destruction and the chronic inflammation process, caused by release of bone destruction markers and inflammatory factors including adipokines in the joint. Besides medications, an additional pain relief is achieved by the treatment of patients with low-dose ionising radiation, either as local low-dose radiation therapy (LDRT) or whole-body exposure to radon in radon baths or galleries. Objectives: In the previous work we showed the decrease of serum levels of visfatin and serum carboxy-terminal collagen crosslinks of type-I collagen (CTX-I) in patients treated in radon baths. 1 In the present study, we analysed serum samples of patients with MSD, who had been treated locally with photon radiation (LDRT). In addition, we analysed differentiation and activity of osteoclasts that were differentiated in vitro from patient-derived monocytes. Methods: Serum samples were collected from patients before and after treatment. Levels of visfatin and CTX-I were measured by ELISA. Monocytes were isolated from blood samples of patients and cultivated with M-CSF and RANKL on bone slices for 2 weeks. Osteoclasts were defined as TRAP and F-actin positive cells. TRAP activity was measured in the cell supernatants using TRAP Staining Kit. Results: In the serum of patients treated with LDRT, a trend to reduced concentration of CTX-I was observed directly after the therapy. Further, osteoclasts, differentiated in vitro from LDRT patient-derived monocytes, showed reduced TRAP activity. Conclusions: The observations made in this study so far substantiate that the radiation-induced decrease of CTX-I levels could be one main factor that is related to the attenuation of inflammation and to the decrease of disease activity in the patients with MSD. This hypothesis is endorsed by the observed reduced differentiation and activity of in vitro cultivated patient-derived osteoclasts. Reference: . Cucu Shreder, et al. Front. Immunol2017;8:882. Acknowledgements: This work was supported by the German Federal Ministry of Education and Research (grant no. 02NUK017A and 02NUK017G, GREWIS), by Landesamt für Gesundheit und Lebensmittelsicherheit Bayern, and by Bayrisches Staatsbad Bad Steben GmbH. Disclosure of interest: None declared